2018
DOI: 10.1080/03007995.2018.1519502
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between inferior vena cava ultrasound, lung ultrasound, bioelectric impedance analysis, and natriuretic peptides in chronic heart failure

Abstract: Evaluation of congestion in outpatients with chronic HF may be based on NTproBNP, IVC ultrasound, or lung ultrasound; they are useful in identifying patients at high risk of hospitalization or death due to HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 45 publications
0
27
0
5
Order By: Relevance
“…In another study, in which LUS findings, IVCUS findings, and N‐terminal pro‐BNP levels of 99 patients with HF were monitored on an outpatient basis for 1 year, and the rates of hospital admission and death were calculated, patients who were hospitalized or died were compared with those who remained stable for HF for 1 year. As a result, patients who were admitted to the hospital or died of HF had significantly more numerous B‐lines on LUS imaging, had significantly greater inspiratory and expiratory IVC measurements, had a lower IVCCI, and had significantly greater N‐terminal pro‐BNP levels 29 . Our study revealed that the IVCCI was greater in patients discharged from the ED than those admitted to the hospital (23 ± 12 versus 18 ± 9).…”
Section: Discussionmentioning
confidence: 63%
“…In another study, in which LUS findings, IVCUS findings, and N‐terminal pro‐BNP levels of 99 patients with HF were monitored on an outpatient basis for 1 year, and the rates of hospital admission and death were calculated, patients who were hospitalized or died were compared with those who remained stable for HF for 1 year. As a result, patients who were admitted to the hospital or died of HF had significantly more numerous B‐lines on LUS imaging, had significantly greater inspiratory and expiratory IVC measurements, had a lower IVCCI, and had significantly greater N‐terminal pro‐BNP levels 29 . Our study revealed that the IVCCI was greater in patients discharged from the ED than those admitted to the hospital (23 ± 12 versus 18 ± 9).…”
Section: Discussionmentioning
confidence: 63%
“…Experts’ comments [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ,…”
Section: Recommendationsunclassified
“…A prospective study compared multiple techniques including IVC diameter, lung ultrasound, bioimpedance analysis, and NT-proBNP to monitor a cohort of HF patients. On multivariate analysis, they found that IVC collapse, NT-proB-NP, and lung ultrasound, but not bioimpedance analysis, were useful in predicting patients at high rates of readmission [16]. New prospective data were recently published, which studied IVC diameter and CI at discharge and hospital follow-up, concluded that larger IVC diameters with less collapsibility were significantly associated with 90-day readmission [17].…”
Section: Evaluation Of Hfmentioning
confidence: 99%